German and Italian activities in Northern Spain (report)
012b-0045-003 - 2 - The preparation of new barracks has been ordered for the Italian forces, whose arrival, in a short time, has been announced. The large building of BATZOKI of RENTERIA (GUIPUZCOA), until now occupied by "Falange Española", has been emptied to provide barracks for the troops which have already arrived and are provisionally occupying some factories. In the RIOJA region, in the south of the Basque Country, about 100 miles from the frontier, the Italians are again taking over the barracks and storehouses which they used during the Civil War. These barracks are regarded as 'rest' barracks. Coincident with the occupation of the frontier by Spanish troops, reports from VITORIA indicate the passage of uniformed Italian officers towards the French frontier. It is expected that in a few days time about 500 new officers for the Spanish army will be nominated after necessary studies at the Military Academy, the direction of which is under control of German and Italian military technicians. Great activity Is being observed these days at the Italian Cartographic centre in VITORIA, where new material is being collected. Reports connect these activities with the new arrival of Italian officers and the concentration of Spanish troops in the northern frontier area. War Material. A new type of armoured car has been unloaded from the German steamer, "Stanleck", at PASAJES. The cars, which are fitted for carrying anti-aircraft guns, are built on three axles, one of which is placed at the centre of the chassis. The wheels attached to this centre axle are half a metre higher than the other wheels, and are intended for use if and when the car becomes stuck on rough ground. It has been established that 600 German aeroplane engines are stored in the cellars of a textile warehouse at LEON. 292/946/12b/45(iii)